2022
DOI: 10.7759/cureus.31347
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between HbA1c Levels and Mortality Rates in Hospitalized COVID-19 Patients

Abstract: Throughout the coronavirus disease 2019 (COVID-19) pandemic, multiple factors have been associated with poor prognosis for those infected by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. Age, obesity, and medical comorbidities have been linked to poor outcomes, including admission to the intensive care unit (ICU), acute renal failure, stroke, myocardial infarction (MI), mechanical ventilation, and even death for hospitalized COVID-19 patients. Although diabetes mellitus (DM) has also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…Previous studies have found varying associations between HbA1c and COVID‐19‐related outcomes 3,18,21,23,24 . A large English study in primary care described a clear association between higher HbA1c in patients and COVID‐19‐related death, 3 but several other studies, including the present, have not been able to reproduce these findings 18,21,23,24 . In contrast, most previous studies have found an association between low HbA1c and high mortality 18,25,26 .…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Previous studies have found varying associations between HbA1c and COVID‐19‐related outcomes 3,18,21,23,24 . A large English study in primary care described a clear association between higher HbA1c in patients and COVID‐19‐related death, 3 but several other studies, including the present, have not been able to reproduce these findings 18,21,23,24 . In contrast, most previous studies have found an association between low HbA1c and high mortality 18,25,26 .…”
Section: Discussioncontrasting
confidence: 70%
“…3,18,21,23,24 A large English study in primary care described a clear association between higher HbA1c in patients and COVID-19-related death, 3 but several other studies, including the present, have not been able to reproduce these findings. 18,21,23,24 In contrast, most previous studies have found an association between low HbA1c and high mortality. 18,25,26 19 SGLT-2 inhibitors, GLP-1 receptor agonists and metformin have been found to be associated with better outcomes.…”
Section: Previous Studies Have Found Varying Associations Betweenmentioning
confidence: 52%